2021
DOI: 10.1089/jmf.2020.0139
|View full text |Cite
|
Sign up to set email alerts
|

Black and Green Tea as Well as Specialty Teas Increase Osteoblast Mineralization with Varying Effectiveness

Abstract: Many human studies suggest a benefit of tea consumption on bone health. The study objective was to compare the ability of different tea types to promote mineralization. Saos-2 cells underwent mineralization (5 days) in the presence of tea (white: WT, green: GT, black: BT, green rooibos: GR, or red rooibos: RR; 1 lg/mL of polyphenols) or control. Total polyphenol content (TPC, Folin-Ciocalteu's reagent), antioxidant capacity (2,2-diphenyl-1-picrylhydrazyl [DPPH] scavenging), mineralization (Alizarin Red stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…25 EGCG can also improve the osteogenic differentiation of mesenchymal stem cells in the bone marrow. 68 Overall, this study demonstrated for the first time that local treatment of EGCG can accelerate the fracture healing process, at least in part, via bone morphogenetic protein-2 (BMP-2). 68 Green tea constituents such as catechins, theaflavins, kaempferol and phenolic acids have been seen to have estrogenic effects, which can influence bone health.…”
Section: Bone Health Effectsmentioning
confidence: 76%
See 2 more Smart Citations
“…25 EGCG can also improve the osteogenic differentiation of mesenchymal stem cells in the bone marrow. 68 Overall, this study demonstrated for the first time that local treatment of EGCG can accelerate the fracture healing process, at least in part, via bone morphogenetic protein-2 (BMP-2). 68 Green tea constituents such as catechins, theaflavins, kaempferol and phenolic acids have been seen to have estrogenic effects, which can influence bone health.…”
Section: Bone Health Effectsmentioning
confidence: 76%
“…68 Overall, this study demonstrated for the first time that local treatment of EGCG can accelerate the fracture healing process, at least in part, via bone morphogenetic protein-2 (BMP-2). 68 Green tea constituents such as catechins, theaflavins, kaempferol and phenolic acids have been seen to have estrogenic effects, which can influence bone health. 69 Finally, lead (Pb) and cadmium (Cd) are environmentally toxic metals.…”
Section: Bone Health Effectsmentioning
confidence: 76%
See 1 more Smart Citation
“…Several nutrients, including calcium and vitamin D, as well as various foods and food components have been studied for their bone promoting or supporting effects (10)(11)(12)(13). Tea and its polyphenols-including some herbal teas such as red rooibos (RR)-may promote bone health and mineral production (14)(15)(16)(17). Several epidemiological studies in different countries including Australia, Britain, and Taiwan have also identified positive associations between black or green tea consumption and greater BMD later in life (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…To date, RR tea has not been studied in vivo for potential bone promoting or supporting effects. Also, in vitro, a wide variety of teas derived from Camellia sinensis and herbal teas from other plants such as RR have been shown to increase osteoblast activity and proliferation (16,17); while also having the capacity to decrease osteoclast activity and proliferation (21,22)-possibly by acting as antioxidants and thereby reducing reactive oxygen species (ROS). ROS have been shown to suppress mineralization and increase resorption in vitro (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%